Peran KSPPS Nur Insani Karanganyar Dalam Pengembangan Ekonomi Mikro Berbasis Syariah - Anton Pradigdyo; Muhammad Tho’in; Iin Emy Prastiwi (ITB AAS INDONESIA Surakarta, 2026)
This research aims to analyze the role of KSPPS Nur Insani Karanganyar in providing access to Sharia financing and its contribution to the development of members' micro-businesses. The research method used is descriptive qualitative with data collection techniques through interviews, observation, and documentation. Data analysis was carried out through stages of reduction, data presentation, and drawing conclusions combined with SWOT strategy analysis. The results show that KSPPS Nur Insani plays an important role as an alternative institution for micro-businesses through fast service processes and the use of Sharia contracts. SWOT analysis reveals that the main strength lies in community trust and humanistic services, while the main obstacles are limited human resources and lack of digitalization . The formulated development strategies include service digitalization, human resource capacity building, and strengthening monitoring to mitigate the risk of default.